2000
DOI: 10.1161/01.str.31.9.2189
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Computer-Quantified Carotid Plaque Echogenicity

Abstract: Background and Purpose-We sought to assess the reproducibility, interobserver variability, and application to clinical studies of a new method for the quantitative assessment of carotid plaque echogenicity. Methods-Carotid plaques were scanned with the use of ultrasound, and their images were stored in a computer. They were normalized by assigning certain gray values to blood and adventitia, and the gray scale median (GSM) was used to quantify their echogenicity. The variability between storage media, between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
116
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(126 citation statements)
references
References 60 publications
7
116
0
3
Order By: Relevance
“…9,10,12,21 Only after the introduction of the image normalization did GSM become a highly reproducible index, allowing us to compare images from different scanners by different ultrasonographers and through different peripherals. 11 To establish an indication to treat patients with an echolucent plaque, we should compare the long-term results of the CAS (as emerging from the follow-up of the ICAROS patients) with those of medical therapy and CEA. The ongoing Asymptomatic Carotid Stenosis and Risk of Stroke (ACSRS) study 27 is analyzing the rate of neurological events in patients with echolucent carotid plaques, as measured by GSM, treated with the best medical therapy alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10,12,21 Only after the introduction of the image normalization did GSM become a highly reproducible index, allowing us to compare images from different scanners by different ultrasonographers and through different peripherals. 11 To establish an indication to treat patients with an echolucent plaque, we should compare the long-term results of the CAS (as emerging from the follow-up of the ICAROS patients) with those of medical therapy and CEA. The ongoing Asymptomatic Carotid Stenosis and Risk of Stroke (ACSRS) study 27 is analyzing the rate of neurological events in patients with echolucent carotid plaques, as measured by GSM, treated with the best medical therapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…B-mode scan settings were adjusted as previously described. 11 A 15-second super-VHS video or magneto-optical disk recording was performed to show the vessel and plaque from a longitudinal view. Images were then sent to the coordinating center and transferred onto a personal computer.…”
Section: Carotid Plaque Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphologic classification and the corresponding ultrasound images is shown on Figure 1. In addition to the macroscopic ultrasonic evaluation of echogenicity, the GSM defined that a score is obtained using computer software as a surrogate marker of plaque vulnerability 63,64 . In fact, lipid-rich plaque core is seen in the DU as echolucent, and fibrotic components as echogenic.…”
Section: Plaque Content and Distributionmentioning
confidence: 99%
“…The GSM scale (grayscale median) describes the distribution of grayscale values on a scale from 0 -255. By means of digital processing of stored ultrasound pictures, it is relatively simple to perform normalization based on reference tissue like adventitia (GSM 185 -195) or blood (GSM 0 -5), thereby achieving better reproducibility of the data [22]. It has been demonstrated that the "normalized" GSM values acquired in this way consistently correlate with clinical events, i. e., they describe the risk of stroke connected to the morphological changes of the plaque [23,24].…”
Section: B-mode Imaging For Displaying Plaque Morphologymentioning
confidence: 99%